MONOPHASIC AND THREEPHASIC ORAL CONTRACEPTIVE PILLS, A RANDOMIZED CLINICAL TRIAL ON THEIR SIDE EFFECTS - O. Zare; F. Shahpoorian; M. Kashanian; F. Hosseini (Iran University of Medical Sciences, 2004)
Oral contraceptive pills are the most effective reversible form of available contraceptive methods. Patient's noncompliance in the use of oral contraceptives is due to untoward side effects. Therefore, finding out the differences between monophasic and threephasic oral contraceptive pills in women regarding the most common side effects, a randomized clinical trial study was conducted, in which 314 users of either monophasic or threephasic pills were selected continuously and allocated randomly into two groups (157 in each group). Findings showed that there were not any significant differences between two groups regarding spotting or intermenstrual bleeding, nausea, headache, nervousness, cloasma and changes of weight (decrease or increase). Overall, monophasic and threephasic oral contraceptive pills were similar regarding side effects. But, since threephasic pills mimic the endogenous hormones level in a physiologic menstrual cycle, It can be concluded that preference should be given to threephasic pills. Comparisone of two mentioned pills regarding their therapeutic effects is recommended for further study.